Novos complexos de 'PD'(II): síntese, caracterização e efeito dos ligantes na citotoxicidade e interação com DNA - Rocha, Carolina Valério Barra [UNESP] (2014)
The use of N,S-donor ligands, as well as phenanthrolines, has been widely explored in the preparation of complexes with increased cytotoxicity. Thus, these ligands were employed in the synthesis of new palladium(II) complexes with the aim to obtain compounds displaying good antitumor activity. The choice for using this metal was based on the similarity of its coordination chemistry to that of platinum(II) whose compounds, such as cisplatin and carboplatin, are widely used as antitumor agents. This works presents the synthesis of 4 ligands and 23 Pd(II) complexes. Complexes 1-4 have the general formulae [PdX2(tmdmPz)] {X = Cl, Br, I, SCN; tmdmPz = 3,5-dimethyl-1-methylthiocarbamoylpyrazole}. Complexes 5-23 of the type [PdCl2(NN)] or [Pd(NN)(L)2]Cl2 {NN = 1,10-phenanthroline (phen), 4,7-dichloro-1,10-phenanthroline (Cl2-phen), dipyrido[3,2-a:2’3’-c]phenazine (dppz), 7-methyldipyrido[3,2-a:2’3’-c]phenazine (CH3-dppz), 7-chlorodipyrido[3,2-a:2’3’-c]phenazine (Cl-dppz); L = thiourea (tu), N-methylthiourea (mtu), N,N’-dimethylthiourea (dmtu), N-phenilthiourea (ftu)} have been synthesized. These complexes were characterized by IR spectroscopy, 1H and 13C NMR, elemental analysis and molar conductivity. The complexes were tested against tumor cell lines. Some studies have been made aiming at evaluating their possible interaction with DNA and to establish preliminary structure-activity relationships. For each group of compounds selected experiments were made, including: reaction with guanosine, DNA unwinding, Kb determination, bromide ethidium displacement, thermal denaturation of DNA and partition coefficient of the complexes. The results indicated that cytotoxicity and also DNA binding affinity are influenced by several factors such as electronic distribution, hydrophobic effects and stereochemistry.